Shadow and bone - Bardugo, Leigh; Thompson, Keith (Square Fish/Henry Holt and Company New York, 2013)
Orphaned by the Border Wars, Alina Starkov is taken from obscurity and her only friend, Mal, to become the protegé of the mysterious Darkling, who trains her to join the magical elite in the belief that she is the Sun Summoner, who can destroy the monsters of the Fold